Physicochemical Properties of Zinc and Lactose in Solid Mixtures: Influence of Trituration Process - Fontes, Clarissa; Oliveira, Adriana P.; Batista, João V.C.; Martins, Cleo; Rossi, André; Yapuchura, Enrique R.; Furtado, Priscila; Meireles, Paloma; Capella, Marcia Alves Marques; Picciani, Paulo H.S.; Holandino, Carla (Homeopathy, 2021)
Background Recent experimental results supporting the dynamization process show modification in the characteristics of solid mixtures.Objective The present work aims to evaluate the physicochemical properties of metallic zinc and lactose, evidencing the interactions between all chemical components presented in dynamized solid mixtures by analytical techniques.Methods Mixtures of zinc and lactose (1:9 w/w) were successively triturated at the same proportion according to the Brazilian Homeopathic Pharmacopoeia, receiving the designation of 10−1 – 10−6 (1dH – 6dH). All samples were submitted to the following characterization techniques: Atomic Absorption Spectrometry (AAS), Scanning Electron Microscopy (SEM), X-ray Diffraction (XRD), Differential Scanning Calorimetry (DSC), Thermogravimetry (TG), and Raman Spectroscopy (RS).Results AAS results detected 97.0% of zinc in the raw material, and the triturated zinc lactose system (ZnMet) presented mean values similar to those expected for the physical mixtures: i.e., 9.94%, 1.23%, and 0.11% in the three first proportions (10−1, 10−2, 10−3), respectively. SEM images showed particle size reduction due to the trituration process. The XRD assays of ZnMet 10−3 and 10−6 indicated peak changes at 12.3° and 43.26°, probably associated with modifications of inter-atomic crystalline spacing. The thermal analysis results of dynamized samples suggest modifications in the chemical interaction between zinc and lactose induced by the physical forces applied. RS experiments showed variation in vibration frequencies due to the dynamization procedure, in which marked ZnMet 10−6 spectral modifications were detected at 357, 477, 1086 and 1142 cm−1, and in the wavelength range 860–920 cm−1.Conclusion These results highlight the importance of applying suitable characterization methods to improve our understanding of the properties of homeopathic solid mixtures, whereas the uses of sensitive tools evidence the influence of trituration on the crystalline properties and in the enthalpy variation of dynamized samples.
Keywords: physicochemical; solid mixtures; zinc; lactose; trituration